(untitled) (CSIAM Transactions on Applied Mathematics, 2025)
In this work, we consider the dynamic framework of the ocean-atmosphere (O-A) coupled model with physical boundary conditions at the ocean-atmosphere interface, and this coupled model can be viewed as atmosphere general circulation model coupled with ocean general circulation model. As the initial data and boundary conditions are assumed to meet certain assumptions, by taking advantage of energy estimates method and compactness arguments, we addressed the existence and stability of global weak solutions, the existence and uniqueness of global strong solution to the O-A coupled model.